Interfacial effects of in situ-synthesized Ag nanoparticles on breath figures - Jiang, Xiaoli (Langmuir : the ACS journal of surfaces and colloids, 2010)
In the present study, we introduced Ag nanoparticles into polymer and found for the first time that Ag nanoparticles can induce the formation of breath figure (BF) arrays on polymer surfaces. The effect of Ag nanoparticles has a balance with the BF process, which is influenced by humidity levels and polymers. These nanoparticle-induced BF process involves an interesting interaction between two self-assembly processes on different length scales. The aggregation of Ag nanoparticles on the water/polymer interface might be the key to their inducing ability. Hence, the interfacial-active Ag nanoparticles can be utilized to widen the applications of the BF method and to fabricate a wide variety of novel functionalized porous polymer films